2014
DOI: 10.2174/1389450115666140624112317
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Oxidative Stress Biomarkers

Abstract: Although an increased oxidative stress has been associated with several pathologies, predictive value of circulating oxidative stress biomarkers remains poorly understood. It has been demonstrated that several pathologies underestimated in women, including cardiovascular diseases, develop differently by gender. In this study, conducted on 195 healthy volunteers, we assessed the putative gender difference in prooxidant and antioxidant status. Our results were successful in demonstrating a significant difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
38
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 37 publications
7
38
3
Order By: Relevance
“…Although FRAP and AOPP were found higher only in men of CD4:CD8 < 1 group, females of the inverted phenotype had lower levels of TBARS. Different studies have indicated gender differences in OS profile, including higher antioxidant defences in men, but there is no consensus in this field [64,65]. Age-related increase in production of ROS has been related to the loss of muscle tissue that occurs mainly among men (sarcopenia) and has also been associated with increased IL-6 and CRP [66][67][68].…”
Section: Discussionmentioning
confidence: 99%
“…Although FRAP and AOPP were found higher only in men of CD4:CD8 < 1 group, females of the inverted phenotype had lower levels of TBARS. Different studies have indicated gender differences in OS profile, including higher antioxidant defences in men, but there is no consensus in this field [64,65]. Age-related increase in production of ROS has been related to the loss of muscle tissue that occurs mainly among men (sarcopenia) and has also been associated with increased IL-6 and CRP [66][67][68].…”
Section: Discussionmentioning
confidence: 99%
“…8 As oxidative stress is considered to be associated with the initiation and progression of different systemic diseases caused by vascular endothelial dysfunctions, such as atherosclerosis, hypertension, and cardiovascular diseases, factors such as sex hormones and gender differences are thought to be associated with oxidative stress markers. [9][10][11] For instance, women have generally been reported to have less reactive oxygen species (ROS) and oxidative stress markers than males. 12 Additionally, the antioxidative effects of the female sex hormone estrogen is known to have an anti-inflammatory and endothelial protection role by modulating the release of protective enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…This difference may not necessarily be a result of sex hormones as most of the women in this study were of age to be post-menopausal and Brunelli et al [39] found no significant difference in oxidative stress markers between young and aged women, at least under healthy conditions. In those living with coronary artery disease (CAD), however, older females have increased markers of oxidative stress compared to males with CAD [41], thus under stress conditions, it is possible that sex differences become more pronounced.…”
Section: Discussionmentioning
confidence: 55%
“…One study found that males have lower oxidant levels than females; however, antioxidant levels were similar [39]. Another found no significant difference in oxidative stress between the sexes but did find an effect of diabetes, with otherwise healthy diabetic females having higher levels of oxidative stress [40].…”
Section: Discussionmentioning
confidence: 99%